The Effect of Dissipation on Nonclassical States of the Radiation Field - Leuchs, Gerd; et al. (Laser Physics, 2005)
We point out similarities in the evolution of different types of nonclassical light fields. Generally, Fock and cat states are considered to decay much faster under dissipation than do squeezed states. We connect measurements of the intensity correlation function of nonclassical light to the second moment of the photon number distribution function. It is shown that all these nonclassical fields behave in a similar manner when one is looking at an appropriate property. Finally it is shown how the electronic-detection noise floor, typically present in measurements of the variance of a photocurrent, can be eliminated based upon a procedure that is well-established for intensity correlation measurements. Copyright © 2005 by MAIK "Nauka/ Interperiodica" (Russia).
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.theeff